Semimetallic 2D Defective Graphene Networks with Periodic 4–8 Defect Lines - Gillen, Roland; Maultzsch, Janina (physica status solidi (b), 2025)
Theoretical simulations of the electronic properties of graphene-like 2D carbon networks with a periodic arrangement of defect lines formed by alternating four- and eight-membered rings are presented. These networks can be seen as arrays of armchair-edged nanoribbons (AGNRs), which are covalently connected at the edges. Using a combination of density functional theory and a simple tight binding model, it is shown that the electronic properties of these networks can be understood to arise from the family behavior of the constituting AGNRs, plus a rigid shift due to an “inter-ribbon” coupling across the defect lines. As a result, one class of zero-bandgap semiconducting 2D networks and two classes of semimetallic networks with quasilinear band close to the Fermi energy are found. The formation of closed-ring electron- and hole-like Fermi surfaces due to hybridization across the defect lines offers interesting perspectives of using such defective 2D networks for transport applications or the realization of carbon-based nodal-line semimetals.
CRIS-Team Scopus Importer:2025-05-02
Keywords: carbon networks; defects; density functional theory calculations; electronic properties